GERAKAN SELULUNG SEHAT SEBAGAI UPAYA PREVENTIF TERHADAP PENYAKIT TIDAK MENULAR (PTM) - Wantini, N.N.P.; Nasichah, M. (Buletin Udayana Mengabdi; Vol 23 No 3 (2024): Buletin Udayana Mengabdi, 2023)
Non-communicable diseases (NCDs) are diseases that cannot be transmitted from one person to another by any form of contact. This dangerous disease is the main cause of death in the world, which is 63%. This NCDs occurs due to a combination of two risk factors, those that can be modified such as smoking habits, consuming less vegetables and fruit, lack of exercise, and other unhealthy lifestyles and which cannot be modified such as genetics, age and gender. The “Healthy Selulung Movement as a Preventive Effort Against Non-Communicable Diseases (NCDs)” is a community service activity that is integrated with field work lectures to improve the health status of the people of Selulung Village. The method of implementing this activity is carried out through several stages, preparation, implementation, and evaluation. The results of the activity show that the community is very enthusiastic about participating in the two activities in this program, starting from counseling to early detection of NCDs. This program also aims to increase community participation in the management and prevention of NCDs. Keywords: NCDs, preventive, counseling, early detection